Pollination patterns and plant breeding systems in the Galápagos: a review - Chamorro, Susana (2012)
Despite the importance of the Galápagos Islands for the development of central concepts in ecology and evolution, the understanding of many ecological processes in this archipelago is still very basic. One such process is pollination, which provides an important service to both plants and their pollinators. The rather modest level of knowledge on this subject has so far limited our predictive power on the consequences of the increasing threat of introduced plants and pollinators to this unique archipelago.